Milk Production, Processing and Marketing - Javed, Khalid (IntechOpen, 2019)
Milk is considered as a complete diet for an infant and contains essential nutrients for the development of young mammals. The substances in milk provide energy and antibodies that help protect against infection. Most farmers are paid for the quality and composition of their milk. Whole milk, once approved for use, is pumped into storage silos where it undergoes pasteurization, homogenization, separation, and further processing. Milk is a highly perishable commodity because it is an excellent medium for the growth of microorganisms - particularly bacterial pathogens - that can cause spoilage as well as diseases in consumers. Milk processing allows the preservation of milk for days, weeks, or months and helps to reduce food-borne illness.